Bis{tris[3-(2-pyridyl)-1H-pyrazole]nickel(II)} dodecamolybdosilicate tetrahydrate - Zhang, Xiutang (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, [Ni(C(8)H(7)N(3))(3)](2)[SiMo(12)O(40)]·4H(2)O, consists of a complex [Ni(C(8)H(7)N(3))(3)](2+) cation, half of a Keggin-type heteropolyanion [SiMo(12)O(40)](4−) and two uncoordinated water molecules. The Ni(2+) cation is surrounded in a slightly distorted octahedral coordination by six N atoms from three chelating 3-(2-pyridyl)-1H-pyrazole ligands. In the heteropolyanion, two O atoms of the central SiO(4) group ([Image: see text] symmetry) are equally disordered about an inversion centre. N—H⋯O and O—H⋯O hydrogen bonding between the cations, anions and the uncoordinated water molecules leads to a consolidation of the structure.